The effect of morphemic analysis instruction on ESL secondary school students’ vocabulary development - Varatharajoo, C.; Asmawi, A.; Rengasamy, S.; Sukumaran, S.D.; Sia Seng Lee, W.A.; Raju, S.; Ahmad, Z. (2014)
The aim of this study is to investigate the effect of explicit teaching of morphemic analysis on vocabulary development among ESL low proficiency secondary school students. As the research states that morphology knowledge is vital for decoding complex words, an increase in vocabulary learning was predicted. Learners’ morphology knowledge in this study was assessed based on analytic word formation after the morphemic analysis intervention. The Morpheme Identification Test adapted from Carlisle (2000) was employed to measure the students’ ability to decode morphemic units in English complex words. The paired sample test was employed to report the results of the study.The result showed a higher score on the post test and students have better morphemic decoding skills after the morphemic analysis intervention.Thus, the study points to the benefits of morphemic analysis instruction on students’ vocabulary development.